2012
DOI: 10.1212/wnl.0b013e31824c46d1
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of cognitive impairment in neurocysticercosis

Abstract: Independently of its phase, NC leads to a spectrum of cognitive abnormalities, ranging from impairment in a single domain, to CIND and, occasionally, to dementia. These findings are more conspicuous during active vesicular phase and less prominent in calcified stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 30 publications
1
35
1
2
Order By: Relevance
“…Neurocysticercosis is a leading cause of epilepsy world-wide, which in itself can have secondary effects on cognition. Active neurocysticercosis is recognised as being associated with cognitive impairment, 8 …”
Section: Cognitive Footprint Of Infectious Diseasesmentioning
confidence: 99%
“…Neurocysticercosis is a leading cause of epilepsy world-wide, which in itself can have secondary effects on cognition. Active neurocysticercosis is recognised as being associated with cognitive impairment, 8 …”
Section: Cognitive Footprint Of Infectious Diseasesmentioning
confidence: 99%
“…Patients with both intra-or extraparenchymal NCC can present with psychiatric manifestations such as cognitive decline and depression. [16][17][18][19][20] The literature regarding the frequency of cognitive impairment in NCC is inconsistent and the relationship between cognitive decline and parasitespecific features remains unclear: mild forms of cognitive decline have been described in 45% and 71.9% of patients with NCC, whereas dementia or severe cognitive deterioration were diagnosed in 12.5% and 15.1% of affected individuals. 19,20 Others reported cognitive impairment to a lesser degree (17% and 12.5%).…”
Section: Discussionmentioning
confidence: 99%
“…In some patients NCC develops clinical manifestations many years after the parasite lodges in the central nervous system [4], as either brain inflammation around the parasite or mass effect. It has also been stated that almost any neurological symptomatology may be found, ranging from mild headache or treatable acute seizures to very severe neurological manifestations, such as intracranial hypertension (ICH), dementia, or even death [5][6][7][8]. These assumptions are probably true, since empirical observation has shown that many of these factors are related to a specific clinical manifestation; however, to date there is no definitive study, using appropriate methodology, designed to address the precise role of each of these factors, or the interaction among them, on the development of symptoms or signs due to NC.…”
Section: Introductionmentioning
confidence: 99%